Assessment of genetic variability, heritability and genetic advance in Indian mustard (Brassica juncea L.) - Surendra Kumar; Rahul Bhardwaj; SJ Jhambhulkar; Archna Rai; Ramesh; Vikas Khandelwal; Manish Kumar (Journal of Oilseed Brassica, 2026)
Forty-five genotypes of Indian mustard (Brassica juncea L.) were evaluated during rabi 2021-22 under four environmentscreated through different dates of sowing (timely sown 20 Oct. and late sown 20 Nov.) and row to row spacing (normal30 × 10 cm and reduced 20 × 10 cm) i.e. timely sown, normal spacing (E1), timely sown, reduced spacing (E2), late sown,normal spacing (E3), late sown, reduced spacing (E4). Pooled analysis of variance revealed significant differences amonggenotypes, environments and G × E for all the traits. Therefore, analysis of variance carried out separately for eachenvironment which indicated significant difference among all the genotypes for 14 traits under all environments. Thevariability studies showed high phenotypic (PCV) and genotypic (GCV) coefficient of variation for number of siliquaeper plant, seed yield per plant and first branch initiation height in all the environments (except in E4 for first branchinitiation height), whereas, moderate GCV and PCV were recorded for plant height, primary branches per plant, 1000-seedweight, number of seeds per siliqua and harvest index in all the environments. Estimate of high heritability along withhigh genetic advance as per cent of mean were observed for number of siliquae per plant, seed yield per plant, firstbranch initiation height, plant height, number of primary branches per plant, 1000-seed weight, number of seeds persiliqua and harvest index in all the environments. Likewise, siliqua length had high heritability along with moderategenetic advance as per cent of mean considered for all the four environments. Thus, these characters might be under thecontrol of additive gene action and direct selection based on these traits could be advantageous.